2010
DOI: 10.1287/msom.1090.0283
|View full text |Cite
|
Sign up to set email alerts
|

Alliance Formation Among Perfectly Complementary Suppliers in a Price-Sensitive Assembly System

Abstract: Independent parties that produce perfectly complementary components may form alliances (or coalitions or groups) to better coordinate their pricing decisions when they sell their products to downstream buyers. This paper studies how market demand conditions (i.e., the form of the demand function, demand uncertainty, and price-sensitive demand) drive coalition formation among complementary suppliers. In a deterministic demand model, we show that for an exponential or isoelastic demand function, suppliers always… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 31 publications
2
41
2
Order By: Relevance
“…Huang and Ke [24] considered a pricing competition and cooperation problem in a two-echelon supply chain with one common manufacturer and duopoly retailers. Yin [25] formulated different supplier alliance models to determine wholesale pricing. Based on the newsvendor model, Krishnan and Winter [26] discussed the cooperation problem of the supply chain under a dynamic environment.…”
Section: Supply Chain Cooperation and Optimizationmentioning
confidence: 99%
“…Huang and Ke [24] considered a pricing competition and cooperation problem in a two-echelon supply chain with one common manufacturer and duopoly retailers. Yin [25] formulated different supplier alliance models to determine wholesale pricing. Based on the newsvendor model, Krishnan and Winter [26] discussed the cooperation problem of the supply chain under a dynamic environment.…”
Section: Supply Chain Cooperation and Optimizationmentioning
confidence: 99%
“…For example, we show that there are infinitely many SPNEs whereas there is a unique SPNE in the lower advertisement revenue regime. [15] also concluded that the the push interaction is not socially optimal since the price quoted to the end-users never becomes 0. However, our analysis shows that in the high advertisement revenue regime, the payment that each end-user incurs becomes 0.…”
Section: E Related Literaturementioning
confidence: 99%
“…Joint selling of complementary components has been studied recently in operations management; see, e.g., Granot and Yin (2008), Nagarajan and Bassok (2008), Sošić (2009), andYin (2010). However, these papers assume a monopolist supplier for each of these complementary components, which leads to a unique final product.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This stability concept is often interpreted as a necessary condition for network equilibrium and proves very useful in many applications such as social relationships, partnerships, and coauthorships (see, e.g., Jackson 2005, Ilkilic 2010). Pairwise stability has also been used in studying coalition formation games in operations management (see, e.g., Granot and Yin 2008, Nagarajan and Sošić 2008, Yin 2010, Fang and Cho 2014.…”
Section: Model Frameworkmentioning
confidence: 99%